The multifunctional Ca2+/calmodulin-dependent kinase IIδ (CaMKIIδ) regulates arteriogenesis in a mouse model of flow-mediated remodeling - Scott, Jason A.; Klutho, Paula J.; Accaoui, Ramzi El; Nguyen, Emily; Venema, Ashlee N.; Xie, Litao; Jiang, Shuxia; Dibbern, Megan; Scroggins, Sabrina; Prasad, Anand M.; Luczak, Elisabeth D.; Davis, Melissa K.; et al. (PLOS ONE, 2013)
Objective: Sustained hemodynamic stress mediated by high blood flow promotes arteriogenesis, the outward remodeling of existing arteries. Here, we examined whether Ca2+/calmodulin-dependent kinase II (CaMKII) regulates arteriogenesis. Methods and Results: Ligation of the left common carotid led to an increase in vessel diameter and perimeter of internal and external elastic lamina in the contralateral, right common carotid. Deletion of CaMKIIδ (CaMKIIδ−/−) abolished this outward remodeling. Carotid ligation increased CaMKII expression and was associated with oxidative activation of CaMKII in the adventitia and endothelium. Remodeling was abrogated in a knock-in model in which oxidative activation of CaMKII is abolished. Early after ligation, matrix metalloproteinase 9 (MMP9) was robustly expressed in the adventitia of right carotid arteries of WT but not CaMKIIδ−/− mice. MMP9 mainly colocalized with adventitial macrophages. In contrast, we did not observe an effect of CaMKIIδ deficiency on other proposed mediators of arteriogenesis such as expression of adhesion molecules or smooth muscle proliferation. Transplantation of WT bone marrow into CaMKIIδ−/− mice normalized flow-mediated remodeling. Conclusion: CaMKIIδ is activated by oxidation under high blood flow conditions and is required for flow-mediated remodeling through a mechanism that includes increased MMP9 expression in bone marrow-derived cells invading the arterial wall.